Access to Firearms as an Element of Political Positioning of the Democratic Party and the Republican Party during the 2016 US Presidential Elections - Borówka, Aleksy (Historia i Polityka, 2019)
The aim of the paper is to identify and describe the policy positioningof the Democratic Party and the Republican Party as concerns access to firearms duringthe 2016 presidential election in the USA. The material analyzed includes official political platforms of both parties and statements of presidential candidates on access to firearms issued during the presidential campaign. The main research method used is content analysis. Based on the conducted analysis, numerous differences and similarities were identified between elements of the political product of “Firearms access” as well as in the (self)positioning of the two parties in relation to the issue. The results point to the significance of the problem of access to firearms as a political product strongly stratifying the American society, a true line of partisan divide. The added value of the article is highlighting the importance of the issue of firearms access in the American political culture, markedly influencing the American political market.